THE ROLE OF THE FAMILY IN THE FORMATION OF CHILD PSYCHOLOGY - Muminova Dinara Shamilovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article analyzes the relationship between children and parents as a pressing problem of our time. During these relationships, various mental processes and misunderstandings between parents and children are observed in the child’s psychology. Psychological recommendations are also given to parents regarding raising a child in the family.